2015
DOI: 10.4315/0362-028x.jfp-14-379
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Inactivation of Salmonella Kentucky Isolated from Chicken Carcasses: Evaluation of Strain Variation

Abstract: The current study was undertaken to evaluate chlorine resistance among strains of Salmonella Kentucky isolated from chicken carcasses. Selected strains (n = 8) were exposed to 30 ppm of chlorine in 10% buffered peptone water (pH 7.4) for 0 to 10 min at 4°C and 150 rpm. The initial level (mean ± SD) of Salmonella Kentucky was 6.18 ± 0.09 log CFU/ml and did not differ (P > 0.05) among strains. A two-way analysis of variance indicated that the level of Salmonella Kentucky in chlorinated water was affected (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…This suggests that the Campylobacter isolate used in testing is an important variable to be considered when assessing the effect of intervention steps in poultry processing. This is in agreement with other reports using Salmonella Kentucky and S. Typhimurium which concluded that the strain of Salmonella is an important independent variable for inclusion in models (Mohamed et al, 2015;Oscar et al, 2013). Differences in inactivation curve shape were noted for some CCs.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the Campylobacter isolate used in testing is an important variable to be considered when assessing the effect of intervention steps in poultry processing. This is in agreement with other reports using Salmonella Kentucky and S. Typhimurium which concluded that the strain of Salmonella is an important independent variable for inclusion in models (Mohamed et al, 2015;Oscar et al, 2013). Differences in inactivation curve shape were noted for some CCs.…”
Section: Discussionsupporting
confidence: 92%
“…Different former investigations tested much higher chlorine concentrations to disinfect different organic material such as carcasses or seeds contaminated with Salmonella spp. with more or less success [57,58]. All authors reported on the chlorine resistance of different Salmonella strains, thereby demanding future detailed investigations on disinfection strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Which organic material is disinfected by chlorination seems to be decisive, but in contrast the temperature seems to have no influence on Salmonella survival [57,[59][60][61]. Organic materials with high protein contents are prone to promote bacterial survival, as especially amino acids (aa) are binding free chlorine molecules, thus reducing their ability to kill bacteria [58]. Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%